2021
DOI: 10.23887/mi.v26i3.39024
|View full text |Cite
|
Sign up to set email alerts
|

Peran Orang Tua dalam Meningkatkan Motivasi Belajar Siswa di Masa Pandemi COVID-19

Abstract: Pandemi covid-19 memberikan dampak terhadap Pendidikan, yaitu salah satunya rendahnya motivasi belajar siswa. Penelitian ini bertujuan untuk menganalisis peran orang tua dalam meningkatkan motivasi belajar siswa. Jenis penelitian adalah penelitian kualitatif. Penelitian dilakukan di kelas IV Sekolah Dasar, dengan subjek 3 siswa dan 3 orang tua siswa. Metode pengumpulan data menggunakan wawancara, observasi, dan dokumen. Analisis data menggunakan analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
6
0
4
Order By: Relevance
“…In the research conducted by other researcher, it is explained that role playing techniques are effective to increase the motivation of students at SMA BPI 1 Bandung in the 2015/2016 school year (Suntani et al, 2021). It can be seen from previous research that found role playing techniques are effective for increasing motivation so that this learning model can overcome and prevent bullying and cyberbullying behavior among elementary school students in the future (Hamidah & Putra, E., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted by other researcher, it is explained that role playing techniques are effective to increase the motivation of students at SMA BPI 1 Bandung in the 2015/2016 school year (Suntani et al, 2021). It can be seen from previous research that found role playing techniques are effective for increasing motivation so that this learning model can overcome and prevent bullying and cyberbullying behavior among elementary school students in the future (Hamidah & Putra, E., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Peran orang tua yang kelima yakni menjadi motivator selama proses pembelajaran daring berlangsung. Pemberian motivasi dalam proses pembelajaran daring sangatlah dibutuhkan untuk meningkatkan minat belajar siswa (Hamida & Putra, 2021;Wiradarma et al, 2021). Kegiatan pembelajaran daring yang dilakukan dari rumah cenderung menyebabkan kebosanan serta kejenuhan bagi siswa (Pawicara & Conilie, 2020).…”
Section: Pembahasanunclassified
“…In today's digital era, the family is the first and foremost environment for children and adolescents so that it has a major influence on children which has a great influence on the formation of behavior, disposition, morals, character and education of the child (Annisa et al, 2020;Arnold & Reed, 2019;Baharun & Finori, 2019). Parenting requires the proper role of the parents, thus the need for a good relationship between the child and the parents (Hamidah & Putra, E., 2021;Patrikakou, 2016;Rindawan et al, 2020). In particular, lack of warmth, positive relationships of children with parents, uncomfortable closeness, violence, inflexibility, rigidity or inconsistent disciplinary practices, insufficient supervision and involvement in children, marital problems, mental health conditions are influential inparenting (Havighurst et al, 2013;Purnama et al, 2022;Wardhani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions in the relationship of parent and child have many factors that affect parenting. This requires the full role of parents in good childcare, so parents need to increase knowledge about the roleof parenting (Hamidah & Putra, E., 2021;Mardiani, 2021). Improper parental care can cause problems in children such as smoking, drinking, consuming illegal drugs, promiscuous sex, not thinking about the future, and can even cause hatred for parents.…”
Section: Introductionmentioning
confidence: 99%